Alteration of sphingosine‐1‐phosphate with aging induces contractile dysfunction of colonic smooth muscle cells via Ca2+‐activated K+ channel (BKCa) upregulation. Issue 5 (16th January 2021) - Shen, Xiaoxue; Zhang, Ling; Jiang, Ling; Xiong, Wenjie; Tang, Yurong; Lin, Lin; Yu, Ting
Abstract: Background: Age‐associated changes alter calcium‐activated potassium channel (BKCa ) expression of colon. Sphingolipids (SLs) are important cell membrane structural components; altered composition of SLs may affect BKCa expression. This study investigated the mechanism by which sphingosine‐1‐phosphate (S1P) contributes to age‐associated contractile dysfunction. Methods: Fifty male Sprague Dawley rats of different ages were randomly assigned to five age‐groups, namely 3, 6, 12, 18, and 24 months. BKCa expression, S1P levels, and phosphorylated myosin light chain (p‐MLC) levels were tested in colonic tissues. In the absence and presence of S1P treatment, BKCa expression, p‐MLC levels, and intracellular calcium mobilization were tested in vitro. BKCa small interfering RNA (siRNA) was used to investigate whether p‐MLC expression and calcium mobilization were affected by BKCa in colonic smooth muscle cells (SMCs). The expressions of phosphorylated protein kinase B, c‐Jun N‐terminal kinases (JNKs), extracellular‐regulated protein kinases, nuclear factor kappa‐B (NF‐κB), and protein kinase Cζ (PKCζ ) were examined to investigate the correlation between S1P and BKCa . Key Results: Sphingosine‐1‐phosphate levels and sphingosine‐1‐phosphate receptor 2 (S1PR2) and BKCa expressions were upregulated and p‐MLC expression was downregulated in the colonic tissues, age dependently. In the cultured SMCs, S1P treatment increased BKCa expression and reduced calcium concentration and p‐MLC was observed. BKCa siRNA increased calcium concentration, and p‐MLC levels significantly compared with control. We also showed that S1P upregulated BKCa through PKCζ, JNK, and NF‐κB pathways. Conclusions and Inferences: In conclusion, S1P and S1PR2 participate in age‐associated contractile dysfunction via BKCa upregulation through PKCζ, JNK, and NF‐κB pathways. Abstract : Aging alters S1P contents, which in turn activates S1PR2 and consequently induces BKCa upregulation via the PKCζ/JNK/NF‐κB‐mediated pathways, thereby causing contractile dysfunction of the colonic SMCs.